Serum retinol-binding protein 4 in stroke patients: correlation with T helper 17/regulatory T cell imbalance and 3-year cognitive function decline - Wang, Fei; Qin, Yaqin; Li, Zongyou (Frontiers in Neurology, 2023)
Objective: Retinol binding protein 4 (RBP4) promotes atherosclerotic progression and neuronal loss, whereas its linkage with cognitive impairment in stroke is unclear. Hence, this prospective study aimed to explore the association of serum RBP4 with the T helper (Th)17/regulatory T (Treg) cell ratio and its correlation with cognitive impairment in stroke patients. Methods: Peripheral blood samples from 265 stroke patients and 50 healthy controls (HCs) were collected at enrollment for serum RBP4 (via enzyme-linked immunosorbent assay) and Th17 and Treg cell (via flow cytometry) determination. Additionally, stroke patients underwent routine follow-up, and their mini-mental state examination (MMSE) scores were assessed at baseline and in the 1st/2nd/3rd years after enrollment. Results: Serum RBP4 was elevated in stroke patients compared to HCs (P<0.001), with a good ability to differentiate stroke patients from HCs (area under the curve: 0.815). Serum RBP4 was positively linked with Th17 cells (P<0.001) and the Th17/Treg cell ratio (P<0.001) and negatively related to Treg cells (P=0.003) in stroke patients, while it was only positively associated with the Th17/Treg cell ratio (P=0.027) but not Th17 (P=0.075) or Treg (P=0.130) cells in HCs. Furthermore, increased serum RBP4 was linked with decreased MMSE score (P<0.001) and cognition impairment incidence (P=0.005) at enrollment in stroke patients, as were Th17 cells and the Th17/Treg cell ratio (all P<0.050). The 1-/2-/3-year MMSE scores in stroke patients were 25.9±2.0, 25.3±2.3, and 24.9±2.3, respectively. More importantly, serum RBP4 was negatively correlated with 1-/2-/3-year MMSE scores (all P<0.001) and positively related to 1-year (P=0.013), 2-year (P=0.007), and 3-year (P=0.001) MMSE score declines in stroke patients. Conclusion: Serum RBP4 is positively linked with Th17/Treg cell imbalance and, importantly, reflects cognitive function deterioration within 3 years in stroke patients. Thus, early and timely interventions and physical rehabilitations are more necessary in stroke patients with a high serum RBP4.